2014
DOI: 10.3390/molecules190811722
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Bisindolylmethane Schiff bases and Their Antibacterial Activity

Abstract: Abstract:In an effort to develop new antibacterial drugs, some novel bisindolylmethane derivatives containing Schiff base moieties were prepared and screened for their antibacterial activity. The synthesis of the bisindolylmethane Schiff base derivatives 3-26 was carried out in three steps. First, the nitro group of 3,3'-((4-nitrophenyl)-methylene)bis(1H-indole) (1) was reduced to give the amino substituted bisindolylmethane 2 without affecting the unsaturation of the bisindolylmethane moiety using nickel bori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…These indoles undergo electrophilic substitution reaction with nitro substituted benzaldehydes in glacial acetic acid for 8 h to produce bisindolylmethanes 1a-1e. The nitro group was being reduced into amine using sodium borohydride/nickel acetate in acetonitrile: water (3:1) (Scheme 1) [36].…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…These indoles undergo electrophilic substitution reaction with nitro substituted benzaldehydes in glacial acetic acid for 8 h to produce bisindolylmethanes 1a-1e. The nitro group was being reduced into amine using sodium borohydride/nickel acetate in acetonitrile: water (3:1) (Scheme 1) [36].…”
Section: Chemistrymentioning
confidence: 99%
“…Some of them are physiologically relevant and therapeutically used [30][31][32]. Bisindolylmethane derivatives, which are prevalent compounds containing two indole rings, have attracted interest of researchers due to their biological activities in recent years [33][34][35][36][37]. Bisindolylmethane is an important class of heterocyclic compound with a variety of pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, imidazole moiety is also considered significant for antiglycation activity as it was found that, free amino group of imidazole ring will competes with amine side groups of proteins in the presence of reactive dicarbonyl compounds (Brownson and Hipkiss, 2000). Benzohydrazides are reported to possess a broad variety of biological activities such as antiglycation (Khan et al, 2013a, b andKhan et al, 2015;Jamil et al, 2015), antioxidant (Aziz et al, 2014;Khan et al, 2012), antileishmanial , antibacterial (Imran et al, 2014), b-glucuronidase , urease and c) and a-glucosidase (Taha et al, 2015f).…”
Section: Introductionmentioning
confidence: 96%
“…Other benzohydrazone derivatives have reported b-glucuronidase ) and aglucosidase inhibition activity . On the other hand, substituted acylhydrazide Schiff bases have shown a broad range of bioactivities, including antiurease , and antibacterial activities (Imran et al, 2014). Hydrazine derivatives also have several commercial applications (Ragnarsson, 2001).…”
Section: Introductionmentioning
confidence: 99%